ANALISIS SEKTOR BASIS DAN NON BASIS DI PROVINSI NANGGROE ACEH DARUSSALAM - AZHAR -; SYARIFAH LIES FUAIDAH; M. NASIR ABDUSSAMAD (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2005)
The study was conducted to identify basic sectors and non basics, and to identify thegrowth of basic and non basic sector from 1992 – 2001 in the Provinsi Nanggroe AcehDarussalam. The data were collected from Badan Pusat Statistik (BPS) and others publishedliteratures regarding to this study. Location Quotient (LQ) and Compounding Factor Analyseswere applied in the study. The results of the study shows that from nine sectors it was knownthat mines sectors, processing industry and agriculture sector are the basic sectors.Meanwhile, others sectors are the non basic sectors. In addition, the study revealed that thegrowth of the basic and the non basic sectors from 1992 – 2001 are fluctuated.